PREVENTION AND TREATMENT OF OSTEOPOROSIS - Castelo Branco, Camil (2015)
Osteoporosis affects women and men, but main1y the feminine sex as a consequence of the hormonal deficit following menopause. The concept of prevention of osteoporosis ¡s complex, and embraces all ages, Primary prevention is directed to stimulate factors of normal bone development so as to reach the maximum peak of bone mass. Secondary prevention is directed to avoíd factors that accelerate the physiologic loss of bone mass. Tertiary prevention is directed to avoid liractures in indivíduals with important decrease of bone mass. The objective of any of these interventions is to ultimately avoid the production of pathological fractures. Based on multiple studies, hygienic-dietary strategies and changes in life-style are broadly justified,- on the other hand, the pharmacological preventive treatment has economic cost and can produce adverse outcomes in certain subjects.